DDT limits of ethanol–air in an obstacles-filled tube - Mendiburu Zevallos, Andrés Armando; Ciccarelli, Gabriel; Carvalho Jr., João A. (Taylor & Francis, 2018)
Experiments were performed to study flame acceleration and deflagration-to-detonation transition (DDT) in ethanol–air mixtures in a tube filled with orifice plates with a blockage ratio of 0.44. Tests were conducted at initial temperatures of 100 and 200°C, and initial pressures of 60 and 101 kPa. Experiments carried out at 60 kPa did not result in DDT, whereas tests performed at 101 kPa, at both 100 and 200°C, resulted in DDT for mixtures in the equivalence ratio range of 1.1–1.3. In a previous study, cell size data of a “double cell structure” have been obtained for mixtures of ethanol–air. Using the d/λ = 1 criterion (that has been confirmed in the tube and orifice plate geometry used in this study with gaseous fuels at room temperature), it was determined that the DDT limit correlates with the ethanol large-cell size reported in the previous study. As a result, for explosion safety purposes, the large-cell size data should be used for assessing the DDT potential of an ethanol–air mixture.
Keywords: Cell size; DDT-Limits; Ethanol; Flame acceleration